The Effects of Traditional Strengthening Exercises Versus Functional Task Training on Pain, Strength and Functional Mobility in Knee Osteoarthritis - Subrat Samal; Shiril Nagarkar; Varsha Pawar; Nitin Samal; Snehal Samal; Krishna Kumar Singh; Vaibhav P (Indian Journal of Forensic Medicine & Toxicology, 2021)
Osteoarthritis (OA) is the most common in India. The incidence of osteoarthritis in adults over the ageof 45. Although there is no evidence to suggest that genetics, heredity, histology and biochemistry play astrong role in its development. To date no cure for the disease exists. However, it has been proven that riskfactors for the onset and progression of disease can be decreased or avoided through lifestyle modificationssuch as weight loss, increased physical activity and dietary changes. Twenty subjects were divided into twoGroups. Training exercise group 7 subjects and functional task training 13 subjects. Baseline measures forperformance outcome measures were insignificant between groups for all of the following: Berg BalanceScale (BBS), (p=0.304), stair climb test (SCT), (p=0.567), timed up and go test (TUG), p=0.970. This studysupport that functional task training is a better option in improving walking speed in this 45-65 year oldpopulation having osteoarthritis knee